Giving Cucumber Infused Water to Reduce High Blood Pressure - Irmaya, Hanny; Hendrawati, Hendrawati; Kamila, Husnun (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Hypertension ranks 6th on the list of Non-Communicable Diseases in Indonesia. The consequences of hypertension if not treated immediately can cause severe damage to body organs. Some conditions of damage associated with hypertension are stroke, heart failure, kidney damage, heart attacks, aneurysms and eclampsia in pregnant women. Cucumber fruit is very good for blood vessels and the heart, where the content of cucumbers that can help lower blood pressure include potassium, magnesium and fastor effectively treat hypertension. Purpose in this study, we analyze the effect of giving cucumber infused water on reducing high blood pressure in the community in Rt 003 Rw 007 Ismaya Cinere, West Java. This type of research is a description with a case study approach model, the sample is 4 respondents who experienced increased blood pressure, with the application of cucumber infused water for 7 days. Results: after 7 days of respondents being given infusion water therapy, there was a decrease in blood pressure from before and after the intervention, the results after the intervention were given the first client's blood pressure: 135/90MmHg, the second client's blood pressure: 125/85MmHg, the third client's blood pressure: 148/85MmHg and the fourth client's blood pressure: 140/95MmHg. Conclusion: cucumber infused water is successful in lowering blood pressure in hypertensive patients.